Investigating the Synergistic Effects of Using Nitrogen and Sulfur Fertilizers on the Growth of Safflower (Carthamus tinctorius L.) - Fattahi, Mostafa; Janmohammadi, Mohsen; Sabaghnia, Naser (Annals of Arid Zone, 2024)
Nutrient imbalance is one of the prevalent problems in the semi-arid region. The study aimed to investigate the effects of sole and simultaneous application of nitrogen and sulfur on safflower yield in a semi-arid region. A field trial was designed to explore the combined use of sulfur (S0: control, S1 and S2: 25 and 50 kg ha-1 S via sulfur phosphate composites, S3 and S4=: 25 and 50 kg ha-1 of S via elemental sulfur, S5 and S6: 25 and 50 kg ha-1 of S via zinc sulfate) and nitrogen (0, 40 and 80 kg ha-1) on the growth and seed production of safflower (Carthamus tinctorius L.) in a west of Iran with mesic active calcixerepts soil that had medium to low fertility. The utilization of large amounts of nitrogen greatly increased the height of the first pod from the ground surface (P ≤ 0.05), and the highest amount was recorded in S 6+ N80 conditions (65%). Leaf chlorophyll content was significantly affected by nitrogen consumption (P ≤ 0.01) and the highest chlorophyll was recorded in S4, S5, and S6 treatments having high levels of nitrogen. A similar trend was observed for the canopy width and the application of nitrogen, zinc sulfate, and elemental sulfur could increase this component by 33%. The highest number of heads was achieved with the use of S5 + N80 and S2 + N80, which was 15% more compared to the control. The application S2 + N80 increased seed number in capitulum by 25% over the control. The application of S along with high levels of nitrogen improved the seed yield by 45% (1334 ± 78.35 kg ha-1). However, only the application of sulfur could improve the harvest index (P ≤ 0.05). The results indicated that applying moderate to high amounts of zinc sulfate and elemental sulfur, in combination with N80, enhanced safflower growth characteristics and improved seed yield components, likely due to synergistic interactions between the elements. Altogether the use of zinc sulfate or elemental sulfur as a logical and effective management solution can increase the efficiency of nitrogen fertilizer and improve nutritional balance.